Analysis of suppression of high-power narrow-band interference in radiometric receivers - Gutsol, T.D.; Cherenkov, A.D.; Semenets, V.V. (Radiotekhnika, 2018)
The subject of this article is analytical analysis of the method and scheme of high-power narrow-band interference suppression in the vicinity of the local oscillator frequency. The used method is based on the automatic detection of interference combined with the local oscillator frequency and maintaining constancy of its signal. Interference cancellation scheme is based on the principle of operation of the modulation radiometer, in which the "meander" voltage switching unit controls the operation of the microwave key, the voltage adders and the phase detector. The circuits of automatic frequency tuning and adjustment of the amplitude of the local oscillator are independent and act continuously.